A beautiful mind - Grazer, Brian, 1953-; Howard, Ron; Goldsman, Akiva; Crowe, Russell, 1964-; Harris, Ed, 1950-; Connelly, Jennifer; Bettany, Paul, 1971-; Goldberg, Adam, 1970-; Hirsch, Judd; Lucas, Josh; Rapp, Anthony; Plummer, Christopher; et al. (Universal, 2002)
Dramatic biography of John Nash, a mathematical genius, who made an astonishing discovery early in his career and stood on the brink of international acclaim. But the handsome and arrogant Nash soon found himself on a painful and harrowing journey of self-discovery. After many years of struggle, he eventually triumphed over his schizophrenia, and finally, late in life, received the Nobel Prize.